A Gǝʿǝz Inscription from Ashkelon - Mulugetta, Meley (Aethiopica, 2004)
An apotropaic Ethiopic inscription was found in the National Park of Ashkelon in 1998, near an absorbtion center for Ethiopian Jewish immigrants (also known as Betä Israʾel). Although the piece is clearly of Betä Israʾel origin, it incorporates symbolisms from Christian or pre-Christian sources, thus demonstrating the syncretic elements in Betä Israʾel religion. The reproduction of Ethiopic prayers of this sort is undoubtedly the last of its kind with the fastly changing religious practices of Betä Israʾel in Israel.